Penerapan Teknologi dan Literasi Digital di SMK Negeri 1 Kendal - Anik Rahmawati; Imtiyaz Farras Mufidah; Agus Triyono; Mursalim Mursalim (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2023)
Information technology is developing rapidly composed the massive dissemination of information in various circles through several channels such as websites, social media, and others. The digital era had a benefical on a number of fields like education, industries, and civilization. However, this also has damaging impacts like the spread of hoaxes, hacking, hate speech, and other harmful digital activities. There are four parameters in the digital literacy assessment, namely: digital skills, digital ethics, digital safety, and digital culture. However, digital culture and security had the lowest index for the last three years. Therefore, Community Service (PkM) activities are needed. The mobility aims to provide socialization regarding the application and technology of digital literacy. The socialization inheld at SMK Negeri 1 Kendal. The material discussed is filtering information or fake news (hoaxes), how digital crime works in taxation, and simulations of how digital crime works and its prevention. The results of these movements confirm that students are enthusiastic about understanding how to filter false information and prevent digital crime and are active in question-and-answer sessions regarding controlling digital crime.